2010
DOI: 10.1016/j.childyouth.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Child Development Accounts and saving for children's future: Do financial incentives matter?

Abstract: This study examines savings outcomes in the first large-scale demonstration of Child Development Accounts (CDAs) in the United States-the Saving for Education, Entrepreneurship, and Downpayment (SEED) initiative. It is also the first empirical study, to our knowledge, to investigate associations between savings outcomes and incentives in an asset-building program for children. This study enhances knowledge about saving in CDAs, incentives in public policy in general, and incentives in savings policy in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…By 2007, SEED participants had accumulated an average of $1,518 toward their long-term goals, including net deposits and the SEED match contribution (Mason et al, 2009). When examining savings among SEED participants, researchers found that, similar to research findings for adults, the total amount saved was significantly predicted by household characteristics such as a single head of household and heads of households with education at the bachelor's level or higher (Mason, Nam, Clancy, Kim & Loke, 2010). In contrast to the weak evidence for race as a predictor of savings among adults (Conley, 1999), Mason and colleagues (2010) found a significant relationship between young people's race and savings amounts.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…By 2007, SEED participants had accumulated an average of $1,518 toward their long-term goals, including net deposits and the SEED match contribution (Mason et al, 2009). When examining savings among SEED participants, researchers found that, similar to research findings for adults, the total amount saved was significantly predicted by household characteristics such as a single head of household and heads of households with education at the bachelor's level or higher (Mason, Nam, Clancy, Kim & Loke, 2010). In contrast to the weak evidence for race as a predictor of savings among adults (Conley, 1999), Mason and colleagues (2010) found a significant relationship between young people's race and savings amounts.…”
mentioning
confidence: 63%
“…However, two studies have examined the relationship between parents' savings and, more generally, young people's amount saved. Mason et al (2010) found that parents' savings was not associated with young people's savings amount. However, these researchers did not examine parents' savings that were designated for young people's use.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations